Proposal for appropriate solutions to reduce influences of sediment dumping activities in the Hai Phong open waters - Vinh, Vu Duy; Hai, Nguyen Minh; Lan, Tran Dinh (Vietnam Journal of Marine Science and Technology, 2019)
Located in the estuary region of the Red - Thai Binh river system, in which the estuarine turbidity maxima occur, the deposition of navigation in waterways to Hai Phong ports is always an urgent problem that needs to be solved. At the present time, it is not easy to use dredged sediment for landfilling or other purposes. Moreover, it is also difficult to dispose of them on the land because of requiring the design and construction of dikes, requiring compaction and drainage of dumped materials. Therefore, disposing of materials at dumping sites in Hai Phong open waters is still an alternative for considering. However, the suspended sediment from the dumping sites can cause influences on the marine environment and ecosystems. Based on the characteristics of natural conditions, socio-economy and ecological environment in Hai Phong coastal areas as well as results of the modeling application (Delft3D model), this paper gives some proposals for appropriate solutions to reduce influences of sediment dumping activities in the Hai Phong open waters. They are: (1) Planning a land for reclamation of dumped materials, (2) Research on the strategies to use dredged sediments as a resource, (3) Finding a best method of dumping, (4) Considering tidal current for daily dumping, (5) Choosing disposal time during neap tide, (6) Restricting disposal in case winds come from SW and S, (7) Reducing time and the number of dumping, increasing amount of sediments in each dumping, (8) Applying technologies in disposal monitoring, (9) Regularly monitoring the environment at the dumping sites and adjacent areas